A novel blockchain-based surveillance and early-warning technology for infectious diseases - Liwei OUYANG; Yong YUAN; Xinhu ZHENG; Jun ZHANG; Fei-Yue WANG (智能科学与技术学报)
The key of early prevention and control of infectious diseases is to use the early warning technology and system to monitor the abnormal occurrence and trend of infectious diseases.There are still some problems in the existing infectious diseases automated-alert and response systems,such as lack of intelligence,poor efficiency in exchange of key information,as well as difficulties in distributed decision-making.Based on the distributed blockchain architecture,a novel blockchain-based surveillance and early-warning technology for infectious diseases was proposed,leveraging emerging information technologies including artificial intelligence,big data and smart contract.The technology could aggregate monitoring forces from multiple parties efficiently,integrate various early warning technologies flexibly,and establish a distributed and collaborative monitoring environment for knowledge integration and intelligent interconnection with guaranteed security and privacy protection.In this framework,smart contract was served as a “software-defined agent” to fuse decisions,monitor the outbreak,and issue warnings in an automatic and real-time fashion,so as to meet the key requirements of accuracy and timeliness,and avoid the decision bias of single evidence.